2006
DOI: 10.1038/sj.ki.5001657
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of cardiovascular events in end-stage renal disease: Results of a randomized trial of fosinopril and implications for future studies

Abstract: Cardiovascular events (CVEs) are the leading cause of death in chronic hemodialysis patients. Results of trials in non-end-stage renal disease (ESRD) patients cannot be extrapolated to patients with ESRD. It is critical to test cardiovascular therapies in these high-risk patients who are usually excluded from major cardiovascular trials. The study objective was to evaluate the effect of fosinopril on CVEs in patients with ESRD. Eligible patients were randomized to fosinopril 5 mg titrated to 20 mg daily (n=196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
215
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(225 citation statements)
references
References 29 publications
5
215
1
4
Order By: Relevance
“…In patients with ESRD, small studies investigating the effect of ACE inhibition on LVH have shown variable results 12, 76. The Fosinopril in Dialysis study (FOSIDIAL), a randomized controlled trial conducted to evaluate the efficacy of fosinopril in helping prevent major adverse cardiac events in patients on dialysis, found no statistically significant difference between the 2 arms in reducing the risk of major adverse cardiac events 83. However, this study was underpowered because of a small sample size, and fewer than expected major adverse cardiac events occurred in the study groups.…”
Section: Chf In Patients With Esrdmentioning
confidence: 99%
“…In patients with ESRD, small studies investigating the effect of ACE inhibition on LVH have shown variable results 12, 76. The Fosinopril in Dialysis study (FOSIDIAL), a randomized controlled trial conducted to evaluate the efficacy of fosinopril in helping prevent major adverse cardiac events in patients on dialysis, found no statistically significant difference between the 2 arms in reducing the risk of major adverse cardiac events 83. However, this study was underpowered because of a small sample size, and fewer than expected major adverse cardiac events occurred in the study groups.…”
Section: Chf In Patients With Esrdmentioning
confidence: 99%
“…In hemodialyzed patients, a prospective controlled trial with the angiotensin-converting enzyme (ACE) inhibitor fosinopril had no significant impact on mortality, although the per-protocol analysis showed a borderline effect (66). Recently, however, some small, underpowered studies showed improved mortality and reduction of cardiovascular events in dialysis patients on candesartan and on different ARB in an unpublished further small multicenter study (56).…”
Section: Primary Preventionmentioning
confidence: 99%
“…After 4 years of follow-up, there were no differences between the two treatment groups in the primary end point of cardiovascular events that included cardiovascular death. 131 Another smaller trial compared candesartan versus placebo in HD patients, but noted a nearly 3-fold reduction in cardiovascular events with active treatment versus placebo. 132 These conflicting results indicate the need for larger studies.…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%